2020
DOI: 10.31025/2611-4135/2020.14030
|View full text |Cite
|
Sign up to set email alerts
|

Tex2mat – Next Level Textile Recycling With Biocatalysts

Abstract: Achieving a circular economy for end-of-life textiles is one of the big challenges in the textile industry. Currently, after disposal, textiles often end up in landfills or in incineration plants. Over the last years, the textile industry exhibited high growth rates and the annual global fibre production is reaching 100 Million t. It also has to be considered that textile products are increasingly becoming more complex, to fulfill special functionality resulting in the use of multi-material textiles. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For this set of tests, the amount of biomass used was 5.33% w/v in a final volume of 30 ml. The pre-treatment was conducted for 2 h at room temperature, without shaking as reported in literature studies [ 14 , 33 ]. To reach a pH 5 the samples were washed and then resuspended in citrate buffer 50 mM overnight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this set of tests, the amount of biomass used was 5.33% w/v in a final volume of 30 ml. The pre-treatment was conducted for 2 h at room temperature, without shaking as reported in literature studies [ 14 , 33 ]. To reach a pH 5 the samples were washed and then resuspended in citrate buffer 50 mM overnight.…”
Section: Resultsmentioning
confidence: 99%
“…Khandaker et al [ 8 ] reported that chemical (pre)treatments can determine efficient bioconversion thanks to the breaking of hydrogen bonds in cotton fibres, resulting in reduced crystallinity and increased amorphous region. For instance, Piribauer et al [ 14 ] reported that alkali pre-treatment of textile waste, combined with a previous mechanical pre-treatment, leads to an increased degradation of cotton in blended cotton-polyester garments up to 83% after enzymatic hydrolysis. Also, Vera et al demonstrated that mechanical pre-treatment in combination with chemical ozone and alkali pre-treatment resulted in glucose recovery yields of 90% after enzymatic hydrolysis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It stands out that very often, textile materials are discarded in landfill sites or incinerating plants [ 17 ], leading to serious environmental risks [ 18 ]. Meanwhile, to reduce environmental impacts, some companies have been adopting strategies to reuse the textile waste [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cotton is one of the most important materials for textile production, but is has raised concerns about its environmental impacts, since its growth and cultivation require large volumes of water and pesticides and its manufacturing involves high levels of energy consumption [ 5 ]. Globally the production of fibres has been growing and reaching levels around 100 million of tons per year [ 17 ]. A large share of this production is directed to supply the textile industry that has also been registering important levels of production growth [ 29 ].…”
Section: Introductionmentioning
confidence: 99%